- Study Helper
Or you could find the KE(gain) and PE(loss). This applies the 'work-energy principle'. That Work Done = change in energy.
So if we have KE(gain) and PE(loss), the total loss of energy = PE(loss) - KE(gain). The Work Done against resistance will be 0, since the resistance is 0 N. So PE(loss) - KE(gain) = 0 or PE(loss) = KE(gain) which is the same as the first example.
So when there is no non-gravitational resistance, using the conversation of mechanical energy. When there is non-gravitational resistance, use the work-energy principle!